Development of Traditional Arts to Increase Tourist Visits of Cultural Reserves in Sobokerti Semarang - Suwarti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Art is the ability to create meaningful works (reviewed in terms of their subtlety, beauty, benefits, form, meaning of form) such as dance, painting and carving. Therefore, the development of traditional arts by increasing tourist visits aims to maintain cultural values ​​that have existed since ancient times so that they do not fade and are forgotten. This research was conducted to determine the development of Sobokarti Traditional arts to increase tourist visits. The method used is descriptive qualitative with an interview process, observation and documentation. The results of the research describe various attractions, facilities, accessibility and ancillaries including the designation as a Cultural Heritage as well as strategies to increase tourist visits so that they are interested in visiting the Sobokarti Semarang Cultural Heritage.